Overview of the Epidemiological Situation on Highly Pathogenic Avian Influenza Virus in Russia in 2018 - V. Marchenko Yu.; N. Goncharova I.; V. Evseenko A.; I. Susloparov M.; E. Gavrilova V.; R. Maksyutov A.; A. Ryzhikov B.; В. Марченко Ю.; Н. Гончарова И.; В. Евсеенко А.; И. Суслопаров М.; Е. Гаврилова В.; et al. (PLoS Medicine, 2019)
Analyzed was modern epidemiological situation on highly pathogenic avian flu in 2018. Prognosis for possible further distribution of viruses in the territory of Russia was made. In 2018, the situation on highly pathogenic avian flu in Russia was challenging. This was due to the spread of the viruses clade 2.3.4.4, which caused multiple outbreaks among wild birds and poultry in European part of Russia. In addition, A/H5N6 avian influenza virus circulation was for the first time detected in the Saratov Region during routine avian influenza virus surveillance. In May, 2018 two different lineages of avian influenza A/H9N2 were isolated during the outbreaks that occurred at several poultry plants in Primorsk Territory and Amur Region of Russia. Subsequently, that virus subtype continued spreading in Russia, which was recorded by detection of the A/H9N2 influenza virus in wild birds in the Khabarovsk and Tomsk Regions of Russia. Thus, it is shown yet again that the territory of Russia plays an important geographical role in the spread of avian influenza viruses. Рассмотрена современная эпидемиологическая ситуация по высокопатогенному вирусу гриппа птиц в 2018 г. и сделан прогноз возможного дальнейшего распространения вирусов на территории России. В 2018 г. в России складывалась неблагополучная эпидемиологическая ситуация по высокопатогенному гриппу птиц. Это связано с распространением вирусов клады 2.3.4.4, которые продолжили вызывать множественные вспышки гриппа среди сельскохозяйственной птицы в Европейской части России. Помимо этого, в ходе мониторинга вируса на территории Саратовской области впервые в России зарегистрирована циркуляция вируса гриппа A/H5N6 клады 2.3.4.4. Весной 2018 г. в Приморском крае и Амурской области впервые также зарегистрирована циркуляция двух различных генетических линий вируса гриппа A/H9N2, которые выделены во время вспышек на территории нескольких птицефабрик. Впоследствии данный субтип вируса продолжил распространяться в России, что зафиксировано детекцией вируса гриппа A/H9N2 у диких птиц на территории Хабаровского края и Томской области. Таким образом, в очередной раз показано, что территория России играет важную географическую роль в распространениивируса гриппа птиц.